Carbothermic reduction of scheelite (CaWO4) doped with cobalt or nickel. (September 2016) - Palmieri, Elena; Marcucci, Andrea; Marcheselli, GianCarlo; De Stefanis, Adriana; Polini, Riccardo
Abstract: Pure scheelite (CaWO4 ) and carbon black mixtures, containing 0 or 2 wt% cobalt or nickel were prepared by 8 or 24 h planetary ball milling (PBM). The mixtures were studied by thermal analysis (TGA-DTA), isothermal annealing at 950, 1000 and 1100 °C, X-ray diffraction (XRD) and scanning electron microscopy (SEM). Independently of the presence of transition metal (Co or Ni), the carbothermic reaction occurs through several steps, where the Ca:O atomic ratio goes from 1:4 to 1:1 according to the sequence: CaWO4  → Ca3 WO6  → CaO, with concomitant development of gaseous CO and formation of metal tungsten. Finally, tungsten is carburized to give nanostructured WC. For the first time we here show that Co and Ni have a noteworthy catalytic effect on the carbothermic reduction of CaWO4 . In particular, these transition metals catalyze both the two-step reduction of scheelite and the subsequent carburization of tungsten. In the latter case, formation of intermediate η phases (Mex Wy Cz, with Me = Co or Ni) occurs. Doping with Co or Ni allows obtaining an almost quantitative (97%) conversion of scheelite into WC after 12 h at a temperature as low as 950 °C. The catalyst allows to reduce PBM duration as well, in that doped mixtures subjected to just 8 h PBM give WC yields larger than 90% after 1 h at 1100 °C, being W2 C the balance. The doping of CaWO4 :C mixtures with few weight percent of Co or Ni allows to produce nanostructured WC by reducing both the milling time and the annealing temperature. These results are particularly appealing from both industrial and sustainability point of view since they allow performing less energy-intensive syntheses of nanostructured WC powders from scheelite. Highlights: Co and Ni have a catalytic effect on the carbothermic reduction of CaWO4 . Co and Ni catalyze both the two-step reduction of scheelite and the subsequent carburization of tungsten. Doping with Co or Ni allows the conversion of scheelite into nanostructured WC at temperatures as low as 950 °C. Adding Co or Ni to CaWO4 :C mixtures allows reducing both the milling time and the temperature of the carbothermic reduction.